Designing a system that removes metallic inclusions from bulk raw materials on the belt conveyor - Zamikhovskіy Leonid; Levytskyi, Ivan; Nykolaychuk, Mykola (Eastern-European Journal of Enterprise Technologies, 2021)
Modern industrial technologies require raw materials of high purity from suppliers, especially due to the possible presence of inclusions of heterogeneous metals in them. The existence of metallic inclusions of heterogeneous metals in the raw materials leads to equipment failure, a decrease in the quality of output products, and, consequently, large financial losses. Since the main method of transporting raw materials in the industry is still a conveyor belt, this imposes additional conditions to control and remove metallic inclusions. For various reasons, current methods for removing metallic inclusions in the conveyor belt do not fully meet the needs of modern production. The main issue related to existing removal systems is the lack of intelligent interaction between these systems and the absence of information exchange between systems that detect and remove metallic inclusions. An alternative method for removing metallic inclusions of heterogeneous metals from loose medium has been proposed, which implies the tandem operation of the system that detects metallic inclusions and the system that removes them. The tandem operation of the two systems makes it possible to exchange information about a detected metallic inclusion and, as a result, to more flexibly use tools for the removal of metallic inclusion depending on the size and location of the metallic inclusion relative to the conveyor belt axis. At the same time, the control unit of the removal system makes it possible to control the conveyor belt itself, which allows the removal of complex metallic inclusions using the reverse of the electric drive of the belt, as well as enables a control check of the fact of removal. The developed algorithm of the removal system was implemented in the programming environment TIA-Portal. The introduction of this removal system could reduce the number of metallic inclusions in raw materials by 15‒20 %; moreover, its application is not limited to only one sector of the national economy